Analisis Aplikasi Augmented Reality dalam Bidang Pariwisata Terhadap Keamanan Privasi Data - Sitepu, Jhoni Ananta; Bryan Michael Kurniawan; Muhammad Rafi Widya Danendra; Nur Aini Rakhmawati (Jurnal Kendali Teknik dan Sains, 2024)
This study investigates the benefits of augmented reality (AR) in the tourism industry and its impact on data security. The background of the research highlights that information technology is becoming increasingly important in the tourism industry, with augmented reality (AR) being a major focus for enhancing visitor experiences. In this context, concerns about user data protection arise since AR applications may require personal information such as user location and travel preferences. A comparative research method was used to compare two popular augmented reality (AR) applications: Smartify, Arts and Culture, Zome, Augmented Reality, Maps AR, Guideo, and AR Trial. The results indicate that most applications have adequate data security policies, including data transfer encryption and user control over their data. Zome was found to be the best in terms of data security and user privacy, scoring 90% in the assessment. This research underscores the importance of using AR applications to maintain data security and user privacy in the tourism industry and suggests further research to learn more about the data privacy practices of AR applications.